G -structure on Kähler manifold - Yasameen Mustafa Abdullah Al-Dulaimi; Ufuk Öztürk; A. A. Shihab (Genius Journals, 2022)
The main goal is to study some questions of the geometry of Kähler manifolds
Keywords: G-structure; structure equations; Kähler manifold; almost complex structure